What are the spatial distribution characteristics of the 4417 landslides in Minhe County, Qinghai Province, China? - Wang, Qinxia; Xu, Chong (Frontiers in Earth Science, 2025)
Landslide relic inventories serve as essential data for geological disaster investigations and risk assessments. Using a previously developed landslide relic inventory for Minhe County, Qinghai Province, this study employs landslide number density (LND) and landslide area percentage (LAP) to thoroughly investigate the spatial distribution characteristics of landslides in the region. Utilizing a GIS platform, we selected ten factors for in-depth analysis, including elevation, slope aspect, slope gradient, relief degree of land surface, distance to faults, lithology, land use type, distance to rivers, rainfall, and NDVI. The results show that at least 5,517 landslide relics have developed in Minhe County, with a total landslide coverage area of 434.43 km2. These landslides are mainly distributed in regions with elevations of 2000–2100 m, slope gradients of 15°–25°, Neogene strata, grassland, and within 0–2 km of rivers. Both slope and aspect are the most significant factors influencing the landslide relics in Minhe County. The findings of this study contribute to a better understanding of the development characteristics and spatial distribution of landslides in the Huangshui River Basin and provide valuable data support for future landslide assessments and disaster prevention efforts.